2012
DOI: 10.1038/nutd.2012.30
|View full text |Cite
|
Sign up to set email alerts
|

Menin and GIP are inversely regulated by food intake and diet via PI3/AKT signaling in the proximal duodenum

Abstract: Background and Aims:Ingestion of food stimulates the secretion of incretin peptides glucose-dependent insulinotropic polypeptide (GIP) and glucagon-like peptide 1 to ensure the proper absorption and storage of nutrients. Menin is the 67 kDa protein product of the MEN1 gene recently reported to have a role in metabolism. In this study, we will determine the regulation of menin in the proximal duodenum by food intake and diet in correlation with GIP levels in the proximal duodenum of mice after an 18 h fast foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…6). Interestingly, Menin was found to respond to feeding and diet in the proximal duodenum, and it plays a negatively regulatory role on the glucose-dependent insulinotropic polypeptide (GIP) by inhibiting of the PI3K/Akt signaling pathway 19 .
Figure 6Mediation by Menin of milk protein synthesis through the PI3K/Akt/mTOR signaling pathway in mammary epithelial cells. Hormones such as insulin and prolactin that acts on epithelial cells modulate the MEN1 /Menin expression level in cells, which further affects the abundance of the factors involved in mTOR signaling and eventually the synthesis of milk protein.
…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…6). Interestingly, Menin was found to respond to feeding and diet in the proximal duodenum, and it plays a negatively regulatory role on the glucose-dependent insulinotropic polypeptide (GIP) by inhibiting of the PI3K/Akt signaling pathway 19 .
Figure 6Mediation by Menin of milk protein synthesis through the PI3K/Akt/mTOR signaling pathway in mammary epithelial cells. Hormones such as insulin and prolactin that acts on epithelial cells modulate the MEN1 /Menin expression level in cells, which further affects the abundance of the factors involved in mTOR signaling and eventually the synthesis of milk protein.
…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have suggested a possible regulatory role for MEN1 /Menin in different tissues through the PI3K/Akt/mTOR signaling pathway 17 19 . Menin was found to directly interact with Akt1 and suppresses its kinase activity by regulating its translocation in the cytoplasm and/or plasma membrane 20 , 21 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the developing stomach, fasting stimulates cell proliferation [138,139] and though corticosterone has been described as part of such effect [140], MAPK action has not been identified yet. In the proximal duodenum, feeding regulates the expression of menin (a 67 kDa protein involved in metabolic control and tumor progression), that in turn inhibits PI3K-Akt signaling, resulting in decreased glucagon-like peptide 1 (GLP-1) secretion and reduced glucose-stimulated insulin release [141]. MAPKs are combined to these pathways in the control of glucose levels, especially through JNK that is extremely decreased or even lost in insulin-resistance [142,143].…”
Section: Nutritional Influence On Cell Signalingmentioning
confidence: 99%
“…The SG þ TB is similar to the duodenal switch (DS) but does not completely exclude the duodenum in order to minimize nutritional complications. The SG þ TB amplifies the nutritive stimulation of the distal gut while diminishing the exposure of the proximal bowel to nutrients without excluding the duodenum and jejunum as has been reported in the literature [5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%